2004
DOI: 10.1101/gad.310304
|View full text |Cite
|
Sign up to set email alerts
|

Increased gene dosage ofInk4a/Arfresults in cancer resistance and normal aging

Abstract: Mammalian genes frequently present allelic variants that differ in their expression levels and that, in the case of tumor suppressor genes, can be of relevance for cancer susceptibility and aging. We report here the characterization of a novel mouse model with increased activity for the Ink4a and Arf tumor suppressors. We have generated a "super Ink4a/Arf" mouse strain carrying a transgenic copy of the entire Ink4a/Arf locus. Cells derived from super Ink4a/Arf mice have increased resistance to in vitro immorta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(129 citation statements)
references
References 40 publications
7
121
0
1
Order By: Relevance
“…This raises the question of whether these increases in p16 Ink4a and p19 Arf expression cause age-related declines in tissue function (Sharpless 2004). Although moderately increased expression of p16 Ink4a and p19 Arf in transgenic mice did not detectably accelerate aging or change life span (Matheu et al 2004), the increase in p16 Ink4a and p19 Arf expression in these mice was small relative to the increase observed in old mice. The levels of p16 Ink4a and p19 Arf that are required to promote aging may be qualitatively higher than the levels that are required to inhibit cancer.…”
Section: The Ink4a Tumor Suppressor May Also Promote Stem Cell Agingmentioning
confidence: 69%
“…This raises the question of whether these increases in p16 Ink4a and p19 Arf expression cause age-related declines in tissue function (Sharpless 2004). Although moderately increased expression of p16 Ink4a and p19 Arf in transgenic mice did not detectably accelerate aging or change life span (Matheu et al 2004), the increase in p16 Ink4a and p19 Arf expression in these mice was small relative to the increase observed in old mice. The levels of p16 Ink4a and p19 Arf that are required to promote aging may be qualitatively higher than the levels that are required to inhibit cancer.…”
Section: The Ink4a Tumor Suppressor May Also Promote Stem Cell Agingmentioning
confidence: 69%
“…The dynamic regulation of the INK4a/b locus is of tremendous importance to tumorigenesis (32)(33)(34)(35)(36), stem-cell maintenance (9,13), cellular senescence (37), and systemic aging (19,38). Here, we have demonstrated that naked mole rat cells express a novel INK4 isoform, pALT INK4a/b , composed of the first exon of p15 INK4b and the second and third exons of p16 INK4a (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The s-p53 mice showed significant decrease in ROS generation and DNA damage. The super-Arf (s-Arf) transgenic mice were generated using a similar method [43]. Since Arf stabilizes p53, dual transgenic Arf/p53 mice were generated by crossing s-Arf and s-p53 mice to study the combined effects of both genes [44].…”
Section: P53 Mouse Modelsmentioning
confidence: 99%